Evaluation of CD4 count and correlation with development of opportunistic infection among HIV seropositives - A, Kumar; S, Singh; NP, Sahu (Eastern Journal of Medical Sciences, 2017)
Background: Opportunistic infections have been the important indicators to suspect and diagnose the HIV seropositives. CD4 count has been used an important tool to monitor the treatment and progression of disease. Methods: This study was done to study the pattern or common presentations of opportunistic infections among HIV seropositive patients and their relationship with CD4 counts. Results: Tuberculosis and candidiasis were the most common opportunistic infections in HIV infected patients followed by herpes, diarrhoea, acute respiratory infection, papular pruritic eruptions, seborrhoeic dermatitis, cryptococcal meningitis, and hepatitis B and C co-infection. Decrease in CD4 count is an important predictor to progression of the disease. Conclusions: This gives a representation of opportunistic infections in HIV seropositive patients in low prevalence state like Jharkhand.